Hepatic haemophagocytosis in haematology patients with hepatic dysfunction: prognostic impact and contribution of liver biopsy combined with the haemophagocytic syndrome diagnostic score (HScore). (15th August 2022) - Bris, Pierre‐Nicolas; Gauchez, Philippe; Devillier, Raynier; Galicier, Lionel; Collignon, Aude; Piana, Gilles; Poizat, Flora; Faucher, Marion; Hospital, Marie‐Anne; Vey, Norbert; Gonzalez, Frederic; Servan, Luca; et al.
Summary: Hepatic dysfunction (HD) is common in patients with haematological malignancies. Hepatic haemophagocytosis (HH) was detected in >50% of liver biopsies taken when HD remained unresolved after standard examination. We aimed to explore the contribution of liver biopsy in patients with both haematological malignancies and HD, describe the population of patients with HH, assess the prognostic impact of HH, and investigate haemophagocytic syndrome diagnostic score (HScore) utility in patients with HH. Between 2016 and 2019, 116 consecutive liver biopsies (76 transjugular, 40 percutaneous) were taken in 110 patients with haematological malignancy and HD (hyperbilirubinaemia, elevated transaminases, and/or cholestasis) and without a clear diagnosis. Liver biopsies were safe and diagnostically efficient. Predominant diagnoses included: HH (56%), graft‐versus‐host disease (55%), associated infections (24%), sinusoidal obstruction syndrome (15%), and tumoral infiltration (8%). Of patients, 35% were critically ill and 74% were allogeneic haematopoietic stem cell transplantation recipients, while 1‐year overall survival (OS) was 35% with HH versus 58% without HH ( p = 0.026). The 1‐year OS was 24% with a HScore of ≥169 versus 50% with a HScore of <169 ( p = 0.019). Liver biopsies are feasible in and contribute significantly to haematology patients with HD. HH occurred frequently and was associated with a poor prognosis. Combined with liver biopsy, the HScore may be helpful in refining haemophagocytic syndrome diagnosis.